2021
DOI: 10.3390/pathogens10111528
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination as a Strategy to Prevent Bluetongue Virus Vertical Transmission

Abstract: Bluetongue virus (BTV) produces an economically important disease in ruminants of compulsory notification to the OIE. BTV is typically transmitted by the bite of Culicoides spp., however, some BTV strains can be transmitted vertically, and this is associated with fetus malformations and abortions. The viral factors associated with the virus potency to cross the placental barrier are not well defined. The potency of vertical transmission is retained and sometimes even increased in live attenuated BTV vaccine st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 125 publications
(179 reference statements)
0
15
0
Order By: Relevance
“…BTV has a high affinity for erythrocytes, 30 but its target cells are endothelial cells, 31 resulting in endothelial damage, vasculitis, edema, and hemorrhage. Pyrexia and anorexia are considered early clinical signs of BTV disease, whereas respiratory distress and esophageal paralysis are considered severe forms of BTV disease 13 . In our study, 71% of sheep exhibited respiratory disease signs, which prompted owners to seek veterinary care.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…BTV has a high affinity for erythrocytes, 30 but its target cells are endothelial cells, 31 resulting in endothelial damage, vasculitis, edema, and hemorrhage. Pyrexia and anorexia are considered early clinical signs of BTV disease, whereas respiratory distress and esophageal paralysis are considered severe forms of BTV disease 13 . In our study, 71% of sheep exhibited respiratory disease signs, which prompted owners to seek veterinary care.…”
Section: Discussionmentioning
confidence: 70%
“…[9][10][11] Disease severity depends on the strain of BTV, with sheep being the most susceptible ruminant species. 12,13 European fine wool and mutton sheep are more susceptible to BTV infections than indigenous breeds, 14 and Hartline/Suffolk crossbred sheep are more susceptible than purebred Hartline sheep. 15 Clinical signs of BTV disease include pyrexia, nasal discharge, congestion of nasal, oral, and ocular mucosa, facial edema, severe mucosal erosions, respiratory distress, coronitis and lameness, cyanosis of the tongue (blue tongue), abortion, and death.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the large number of serotypes, each with varying virulence, it is difficult or impossible to vaccinate livestock against all strains (Noad and Roy [2009]). In addition, recent studies have shown that, due to the segmented genome of BTV, the use of live attenuated viruses to vaccinate ruminants has the possibility of introducing new genetic material to environments, increasing the risk of creating new BTV serotypes (Rojas et al [2021]).…”
Section: Bluetongue (Bt)mentioning
confidence: 99%